INTEGRASI METODE RAPID APPLICATION DEVELOPMENT (RAD) DAN USER ACCEPTANCE TESTING (UAT) DALAM PENGEMBANGAN SISTEM INFORMASI PEMESANAN DIGITAL PRINTING: INTEGRATION OF RAPID APPLICATION DEVELOPMENT (RAD) AND USER ACCEPTANCE TESTING (UAT) METHODS IN THE DEVELOPMENT OF A DIGITAL PRINTING ORDERING INFORMATION SYSTEM - Kenza Amelia Putri Anwarri; Galuh Wilujeng Saraswati; Wildan Mahmud; Erba Lutfina; Resha Meiranadi Caturkusuma (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Advances in information technology have encouraged various business sectors to switch from manual systems to digital systems in order to improve efficiency and service quality. CV. Penanggungan 44, as a digital printing service provider, previously used a manual ordering system, resulting in inefficient transactions and susceptibility to recording errors. This study aims to design and develop a website-based Digital Printing Ordering Information System that can simplify the ordering process and assist in integrated data management. The system was developed using the Rapid Application Development (RAD) method combined with a User-Centered Design (UCD) approach and User Acceptance Testing (UAT) applied iteratively. UAT is not only used as a final testing stage, but also utilized since the interface design stage as a formative evaluation, so that user feedback can be directly integrated into the system design and construction improvement process. This approach ensures that rapid development remains in line with user needs and experiences. Black-box Testing shows that all system features function properly with a 100% success rate. Meanwhile, the User Acceptance Testing (UAT) results obtained an average score of 86.8% in the excellent category, indicating that the system is easy to use and well-received by users. Thus, the developed system is deemed suitable for use in improving operational efficiency and service quality at CV. Penanggungan 44